Pterula bispora (Pterulaceae), a new species distributed in Northeastern and Southwestern China - Sun, Pei-Si; Deng, Peng-Tao; Zhang, Ping (Phytotaxa, 2026)
Pterula bispora sp. nov. (Pterulaceae) is described as a new species based on morphological and molecular evidence from two specimens collected from Guizhou and Jilin provinces, China. This species is distinguishable by its slender branches, darkened apices, and 2-spored basidia. Phylogenetic analysis of a concatenated dataset of internal transcribed spacer (ITS), nuclear ribosomal large subunit (LSU), and RNA polymerase II subunit B gene (RPB2) sequences revealed that the two accessions were nested within the Pterula clade and were grouped together in a distinct subclade, thus supporting their identification as an unnamed species of Pterula. A full description, illustrations, and the results of molecular phylogenetic analyses for the new species are provided.